(untitled) (CAHIERS MAGELLANES-NS, 2024)
Although there is growing awareness of Farmer Producer Organizations (FPOs) as tools of empowerment for rural women, significant barriers continue to hinder their active participation. Socio-cultural constraints, financial risks, and gender-based exclusion are major challenges faced by women in rural India. This study surveyed 250 rural women in Tirupattur District, Tamil Nadu, to identify key obstacles to their involvement in FPOs. The findings reveal that family approval, fear of gender-based violence, and social stigma significantly influence women's willingness to participate. Additionally, practical issues such as lack of financial security and increasing domestic responsibilities further exacerbate these challenges. The study highlights the need for policies to adapt to the local socio-cultural context. It recommends targeted facilitation measures, such as creating safe spaces, providing financial management training, and fostering leadership skills, to enhance women's participation. Such interventions can maximize the potential of FPOs, promoting both social and economic empowerment for rural women.